The Relationships of Learning Styles, Learning Motivation and Academic Success in EFL Learning Context - Srichanyachon, Napaporn (Mediterranean Journal of Social Sciences, 2012)
This paper reports the findings of a survey of learning styles and learning motivation of EFL learners. It aimed to comparelearning styles and motivation to learn English of Bangkok University students categorized by their background, and investigate therelationship among English background knowledge, learning styles, and learning motivation. The samples were 183 undergraduatestudents enrolled in Fundamental English course. The instrument in this study was a questionnaire. Results indicated that the level oflearning styles and learning motivation in general were moderate. There were no statistically significant differences at .05 level found instudents’ learning styles and learning motivation as classified by gender, school type and field of study. As hypothesised, positiverelationships were found among students’ English background knowledge, learning styles, and learning motivation at .05 level, andstudents with higher English background knowledge were found to have a greater variety of learning styles and more motivation to learnEnglish.